Financial education in Secondary Education: a cross-country analysis - López-Agudo, Luis Alejandro; Marcenaro-Gutiérrez, Óscar David (Oxford University Press, 2023)
We live in a society in which knowing how to manage money is a necessity, since it is required in our everyday life. In this context, financial literacy is a competence which people should develop in order to improve their money-related decisions. In order to analyse the contribution of financial education to this competence, we go beyond the previous literature in respect to correlation by using student fixed-effects and PISA 2018 data for 15-year-old students in 20 countries. Our results show that, in most of the countries under analysis, the financial education that students receive in the subject of mathematics may contribute to the development of their financial literacy competences. Nevertheless, the lack of an effective subject in economics is still an issue in most of the educational systems under analysis.
https://academic.oup.com/pages/self_archiving_policy_b
Keywords: Educación financiera - Estudio y enseñanza; Rendimiento académico; PISA 2018; Financial education; Financial literacy; Student fixed-effects